To complete the input-output table for the function \( f(x) = - (x + 1)^2 + 4 \), we need to calculate the outputs for the given x values of -1, 0, 1, and 2.
-
For \( x = -1 \): \[ f(-1) = -(-1 + 1)^2 + 4 = -0^2 + 4 = 4 \]
-
For \( x = 0 \): \[ f(0) = -(0 + 1)^2 + 4 = -1^2 + 4 = -1 + 4 = 3 \]
-
For \( x = 1 \): \[ f(1) = -(1 + 1)^2 + 4 = -2^2 + 4 = -4 + 4 = 0 \]
-
For \( x = 2 \): \[ f(2) = -(2 + 1)^2 + 4 = -3^2 + 4 = -9 + 4 = -5 \]
Now we summarize the results:
| x | f(x) | |-----|------| | -1 | 4 | | 0 | 3 | | 1 | 0 | | 2 | -5 |
From these results:
- \( f(-1) = 4 \)
- \( f(0) = 3 \)
- \( f(1) = 0 \)
- \( f(2) = -5 \)
The largest output value is \( f(-1) = 4 \).
Thus, the x value that produces the largest output for the function is:
x = -1.